Development of green catalytic processes using O2, CO2 and inorganic salts - Wang Xi (The Graduate School, Ajou University, 2014)
It is widely acknowledged that there is a growing need for more environmentally acceptable processes in chemical industry. This trend attract attentions towards what has become known as “green chemistry” which focused mainly on eliminating waste and avoiding the use of toxic and hazardous reagents and solvents in the manufacture and application of chemical products. In order to develop the green catalytic systems, cheap and abundant oxygen, carbon dioxide and inorganic salts were used in this thesis. In Chapter 1, recent reported methods for the oxidation of alcohols and thiols have been reviewed. For the oxidation of alcohols, aerobic oxidation has been mainly discussed, including the transition-metal-catalyzed and transition metal-free aerobic oxidation of alcohols. In addition, we presented a few examples of oxidation reactions using CO2 as a mild oxidant. Also, a brief introduction of thiol oxidative dimerization to disulfides has been reported. We studied the oxidation of alcohols by using CO2 as a mild oxidant in Chapter 2. Compared to previous reported methods for oxidation of alcohols, it avoids the use of large amounts of chemical oxidants and transition metals. In addition, using CO2 as a mild oxidant was limited to heterogeneous catalytic reactions at high temperature and pressure. In this study, we widen the utilization of CO2 in organic synthesis under mild conditions. In Chapter 3, an organic base-mediated carboxylation using CO2 was discussed. The advantage of this reaction is that it avoids the use of large amount of inorganic salts and metal catalysts, which further expand the use of CO2 as carbon source in organic synthesis. Then O2-mediated oxidation of thiols to produce thiocarbonyl compounds was demonstrated in Chapter 4. Instead of using expensive and rarely available reagents, a combination of catalytic amounts of copper complex and organic base by using O2 as oxidant can convert thiols directly to thiocarbonyl compounds. In Chapter 5, ammonium carbonate and various amines coupled with boronic acids in the presence of catalytic amounts of copper complexes, monoarylamines, symmetric and unsymmetric diarylamines were obtained with good yields by this general, versatile and practical protocol.
학위논문(박사)--아주대학교 일반대학원 :에너지시스템학과,2014. 8